2018
DOI: 10.1177/0269216318784474
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning: A systematic review about experiences of patients with a life-threatening or life-limiting illness

Abstract: Background:Advance care planning is seen as an important strategy to improve end-of-life communication and the quality of life of patients and their relatives. However, the frequency of advance care planning conversations in practice remains low. In-depth understanding of patients’ experiences with advance care planning might provide clues to optimise its value to patients and improve implementation.Aim:To synthesise and describe the research findings on the experiences with advance care planning of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
127
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(154 citation statements)
references
References 56 publications
9
127
0
1
Order By: Relevance
“…Conversely, ACP is an important strategy to improve end-of-life communication between patients and healthcare providers. Other potential benefits are that ACP allows patients to maintain a sense of control and gives them the opportunity to incorporate personal preferences [28].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, ACP is an important strategy to improve end-of-life communication between patients and healthcare providers. Other potential benefits are that ACP allows patients to maintain a sense of control and gives them the opportunity to incorporate personal preferences [28].…”
Section: Discussionmentioning
confidence: 99%
“…62 Although some research indicated preferences for earlier discussion, other research found that patients may lack readiness to think about ACP and need time to cope with the initial shock of a diagnosis. 68 For COPD and respiratory illnesses, a lack of knowledge among patients about the terminal nature of COPD could present a challenge to identifying when best to begin ACP discussions. 61,65 Some reviews showed that patients and carers recognized that ACP discussions may be recurring events rather than one-off exercises.…”
Section: Timing Of Acp Discussionmentioning
confidence: 99%
“…Patients could feel respected and heard through ACP but also disrupted and distressed, and some were reluctant to be open with health care professionals as ACP could expose family tensions. 68 In the context of kidney disease, patients felt generally positive about ACP, but one of the main topics of discussion for this groupedecisions about dialysisewas complex and challenging. 39,64 These patients were vulnerable and fluctuated between wanting survival and wanting death; deciding to discontinue dialysis was difficult as some feared being labeled cowardly or upsetting their families.…”
Section: Perceived Value Of Acp Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with findings from a study by Rietjens et al [34] that found that ACP can be initiated at any stage of a person's life, but that it should be more targeted when the health condition worsens. Other studies also show that ACP should be introduced when the individual person is ready [34,[52][53][54]. Both elements are presented in our set of indicators for initiating ACP.…”
Section: Plos Onementioning
confidence: 99%